COVID-19 and Telenutrition: Remote Consultation in Clinical Nutrition Practice - Farid, Doaa (Curr Dev Nutr, 2020)
During the coronavirus disease 2019 pandemic, clinical dietitians, as other clinicians, have had to shift their elective in-person clinical encounters to online consultations. Adequate planning and use of tools are essential to minimize delay in delivering medical nutrition therapy to existing and new clients. This article describes the steps required to launch a successful e-nutrition clinic during these times of crisis. During Covid-19 pandemic, clinical dietitians have had to shift their elective in-person clinical encounters to online consultations. This article describes the steps required to launch a successful telenutrition clinic.